Riscritture appropriate e approprianti. Traduzione e revisione del testo letterario (Altre Modernità, 2012)
Both the translation and the revised version of a literary text give rise to similar issues, for in both cases one can adopt a strategy of either appropriate rewriting or appropriating rewriting. In the former case, the tendency is to respect the properties and peculiar qualities of the Other; in the latter, the tendency is to manipulate and distort the text, to reduce the Other to the Self and not to contemplate the creative potentialities of contaminated language. Italian publishing houses seem to be afraid of hybridity: homologation, order, syntactical and lexical propriety appear more alluring. But it is the two elements of the foreign and the new enclosed in the concept of hybridity that allow the translator to challenge the cultural values of the publishing establishment. Even if liminal space is an unexplored area by the Italian publishing sector, the concept of in-betweeness is very useful for translation, in particular post-colonial translation. One of the fields in which the creative potential of liminal space can be fully explored by translators, revisers and publishers alike is the field of contact languages, for pidgins and creoles move freely in the interstitial zone. An example taken from Jean Rhys’ Wide Sargasso Sea (1966), and its comparison with Adriana Motti’s translation, published by Adelphi in 1971, allow us to show what is meant by appropriate and appropriating rewriting.